Program Development Karang Taruna Dan Digital Marketing Sebagai Upaya Modernisasi Di Era Digital Kelurahan Mulyorejo Kota Malang - Nurohmah, Dilla; Ayu Wardani, Zulfita Senja; Oktavia, Isna; Ariyanti, Ariyanti (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
This study aims to develop creative mindsets and modernization strategies for micro, small and medium enterprises (UMKM) in RW 01, Mulyorejo Village, Malang City through training and digital marketing in the digital era. Karang Taruna in this area has experienced a decline in activity, so revitalization and increased understanding of organizational management are needed. This program uses a participatory approach involving observation, socialization, training, and evaluation. Through organizational management training, Karang Taruna RW 01 succeeded with members who better understand their roles in society. Mentoring for MSMEs is carried out to improve digital marketing skills, such as creating business profiles on social media, using Instagram and Google Maps, and increasing product branding. As a result, MSMEs in RW 01 such as Dapur Mbak Vidho and Jamu Instant Mekar Sari have succeeded in increasing the visibility and sales of their products. In conclusion, digital marketing has a crucial role in supporting the sustainability and innovation of UMKM, as well as contributing to socio-economic development at the local level.